AB0929 The Serum Levels of Cholinesterase and Total Cholesterol PREDICT the Existence or Latency of Multiple Organs' Involvements in Japanese Patients with Igg4-Related Disease. (10th June 2014) - Taniguchi, Y.; Ode, K.; Hirose, K.; Shimamura, Y.; Ogata, K.; Inoue, K.; Horino, T.; Hyodo, M.; Fujimoto, S.; Terada, Y.
Abstract : Background: IgG4-related disease (IgG4-RD) is the new entity, which is a multisystem and fibroinflammatory condition. It is characterized by progressive scarring and dysfunction of affected organs and tissues including the pancreas, hepatobiliary tree, kidneys, salivary glands, retroperitoneum and lungs, etc. New diagnostic imaging methods for IgG4-RD have been sought. Recent several reports showed that FDG-PET/CT scans accurately, and safely identifies the multiple organs' involvements in IgG4-RD patients. Objectives: To evaluate clinical characteristics, including laboratory and FDG-PET/CT findings, of Japanese patients with IgG4-RD. Methods: The clinical symptoms, laboratory, pathological and FDG-PET/CT findings of Japanese patients with IgG4-RD (n=14) were assessed. Several laboratory data of IgG4-RD with multiple organs' involvements (n=7), IgG4-RD with limited organ's involvement (n=7) and, one of hyper-IL-6 syndromes, ANCA-associated vasculitis (n=10) were comparatively examined. All data are presented as mean ± SD. Results: IgG4-RD patients (mean age 68±11; male/female 10/4) had xerostomia and bilateral submandibular glands enlargement. As complication, 3 had bronchial asthma, 2 had chronic thyroiditis and 1 had ulcerative colitis. FDG-PET/CT imaging revealed enlargement and increase of FDG accumulation of the bilateral submandibular glands, mediastinal lymph node, lung, spleen, kidney, periaorta and prostate. Interestingly, a part of these organs was asymptomatic. Follow-up FDG-PET/CT after steroid treatment, with no symptoms, showed a significant decrease in FDG accumulation in IgG4-RD lesions. The serum IgG4 level was 847±711 mg/dl (normal 8-135 mg/dl). Four cases with hypocomplementemia and elevated immunocomplex of 14 IgG4-RD cases revealed renal involvements (tubulointerstitial nephritis), and moreover, these 4 cases also had interstitial lung involvements. Notably, cholinesterase (ChE) and total cholesterol (T-cho) levels in IgG4-RD cases with multiple organs' involvements (n=7) significantly decreased from these levels in IgG4-RD with limited organ's involvement (n=7) and ANCA-associated vasculitis (n=10) ( p <0.05). Conclusions: When we diagnose IgG4-RD, it is important to differentiate hyper-IL-6 syndrome. FDG-PET/CT imaging and measuring serum ChE and T-cho levels might help us not only to evaluate widespread lesions and monitor disease activity in IgG4-RD, but also to differentiate other disorders. Acknowledgements: No funding support Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4250